Elderly Empowerment Diabetic Foot Exercise and Balance Exercise: - Yunus, Emeliawati (Sahabat Publikasi Kuu, 2024)
The simulation of diabetic foot exercises and balance training conducted by the 42nd group of 'Aisyiyah Yogyakarta University's 2024 Community Service Program (KKN) students in Sidoagung hamlet, Godean RW 07 is to improve blood circulation and prevent foot deformities in diabetics. In addition, this balance exercise helps the elderly avoid hypertension, which improves body balance and reduces the risk of falls. In addition, to maintain health and improve the quality of life of the community, this activity is a community service that focuses on health and body balance. The method used is demonstration. The results obtained can increase knowledge to the elderly and be able to do independently at home